FORMING THE MICROBIAL COMPLEX OF TYPICAL BLACK-SOIL IN SPRING BARLEY AGROFITOCENOSIS FOR DIFFERENT AGRICULTURE SYSTEMS - Кіроянц, М. О. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
Microbial coenosis is one of the most diverse and widespread types of spatial-functional organization of living groups on Earth. The article presents the results of studies that rely on the study of the qualitative and quantitative composition of the microbial complex, which transforms the organic matter of typical black soil of spring barley cultivation in various farming systems. The study of the typical microbial flora of the black soil was carried out on the basis of the stationary field experience of the Department of Agriculture and Herbology of NULES of Ukraine "Agronomic Experimental Station". The territory of the studied field is located in the right-bank part of the Forest-Steppe of Ukraine. The experiments were conducted on biological, ecological and industrial systems of agriculture; processing - plowing and superficial; and the system of noutil as a control was also studied. The number of microorganisms of the main physiological and taxonomic groups was determined by the method of sowing soil suspensions on the respective elective nutrient media. In the article a comparative analysis of the formation of the microbial complex of typical blck soil in spring barley agrophytocenoses was conducted. The qualitative composition of the microbial complex was studied on the basis of the representation of morphological and cultural types. According to the results of the analysis, the level of differentiation of the number of major physiological and taxonomic groups of microorganisms of the rhizosphere of plants was studied. One of the main goals of the study is the long-term development, formation and realization of the best agents of the rhizospheric environment of the RSL to optimize the growth and development of barley against the backdrop of reducing the use of mineral fertilizers